America–China Trade War during the Trump Administration: A Confrontation between Strategic Superpowers - Dadda, Largout, Khalifa Dhirar (University of El-oued, 2021)
Increasing economic power of the People’s Republic of China in the course of the recent years alongside the United States’ declining share within the global production, as well as international trade within the start of the 21st C, has resulted in a change within the world's geopolitical landscape and the springing up of the "Group of Two", which can simply be referred to as G2. In 2015, China emerged as the leader within commodity exports thereby becoming a principal player in global trade. As a result, U.S came up with policies that were aimed at slowing down China’s drastic economic growth in the fear that it may overtake it and become the economic giant globally. It is in that line that the U.S has introduced protectionist policies. China was also compelled to come up with its counter policies in response to the American policies that targeted it. The present situation of the America-China trade relations is what is commonly termed as Cold Trade War. In this paper, we take a look at the causes of the Cold Trade War and the possible consequences. All in all, it will be illustrated that in every trade war, there are neither winners nor losers as the countries involved end up losing as it will be outlined in this paper.
Keywords: Economic Power, China, United States, International Trade, Geopolitical, Cold Trade War, Trade War